The perception of university lecturers of teaching and learning in massive open online courses (MOOCS) - Ghazali, Norliza; Nordin, Mohamad Sahari (Faculty of Education, Universiti Kebangsaan Malaysia, 2016)
Massive Open Online Course, better known as MOOC has become a buzzword within the field of education. MOOC is a new teaching innovation and practise of education delivery that targets to promote active learning and develop educational communities including thousands of students. At this early stage, not many research has been done especially in the Malaysian context. This study aims to explore the perception of teaching and learning in MOOC from the perspectives of selected Malaysian public university lecturers who have had the knowledge and experiences in using MOOC. Moreover, this study will explore how MOOCs are being used in teaching and learning as well as the challenges by using MOOC, and also the suggestion for MOOC improvement. The findings show that MOOC provides opportunity for life-long learning via elearning. Lecturers use MOOC in teaching and learning process by integrating video and animation. The study also provided information on the challenges in using MOOC and suggestions for further research for MOOC’s improvement. The current MOOC offering need to be objectively reviewed to ensure that the innovation is relevant for the educational system. Respondents in this study believe that MOOC will bring positive impact in the education system in this technologically-driven environment of the 21st century.